Omega-3 fatty acid deficiency disrupts endocytosis, neuritogenesis, and mitochondrial protein pathways in the mouse hippocampus - English, Jane A.; Harauma, Akiko; Föcking, Melanie; Wynne, Kieran; Scaife, Caitriona; Cagney, Gerard; Moriguchi, Toru; Cotter, David R. (Frontiers in Genetics, 2013)
Omega-3 fatty acid (n-3 FA) deficiency is an environmental risk factor for schizophrenia, yet characterisation of the consequences of deficiency at the protein level in the brain is limited. We aimed to identify the protein pathways disrupted as a consequence of chronic n-3 deficiency in the hippocampus of mice. Fatty acid analysis of the hippocampus following chronic dietary deficiency revealed a 3-fold decrease (p